A rare case of lactation anaphylaxis - Durgakeri, Pramod (Australas Med J, 2015)
Lactation anaphylaxis (LA) is an extremely rare condition with only five other cases having been previously reported in the literature. Patients will exhibit cutaneous symptoms, respiratory symptoms, gastrointestinal symptoms, and/or cardiovascular symptoms. Post-partum, the drop in hormones is thought to facilitate an exaggerated histamine response. An elevated serum tryptase level performed between 15 minutes to three hours of onset of symptoms will confirm a true anaphylactic reaction. It is important to be aware of this extremely rare medical condition and its management with antihistamines. Better awareness and education of medical staff on this very rare phenomenon can help to better manage these patients.